Intergenerational altruism and house prices: evidence from bequest tax reforms in Italy - Giorgio Bellettini; Filippo Taddei; Giulio Zanella (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 2014)
We identify the degree of intergenerational altruism in an OLG framework à la Barro exploiting the quasi-experimental variation generated by reforms of bequest taxation (estate or inheritance tax, in the U.S.) and taxes on inter vivos real estate donations (gift tax, in the U.S.) that were enacted in Italy between 2000 and 2001. Employing a unique data set containing information on the housing stock and house prices in 13 large Italian cities between 1993 and 2004, we identify the structural parameter of interest via the effect of changes in the tax rate on house prices. We find that the intergenerational altruism parameter is about 20%. Given the possible anticipation of the reform this estimate should be interpreted as a lower bound.
Keywords: E60; E65; H24; 330